INTEGRASI UPGRADING SDM DAN BUDAYA KERJA PRODUKTIF DALAM PENGELOLAAN DI BMT AL MUHAMMAD CEPU - Wahyudin, Muhamad (Al Fattah Ejournal Sma Al Muhammad Cepu, 2024)
This study aims to analyze the impact of Human Resources (HR) development in improving organizational performance amid the challenges of globalization and technological changes. As the dynamics of the labor market evolve, companies are required to adapt to current trends, including the adoption of new technologies, flexible work policies, and the development of global leadership. The results of the study show that companies that successfully adjust to these factors are able to significantly improve employee productivity and satisfaction. Furthermore, organizational culture and international regulations also play a crucial role in creating an inclusive and innovative work environment. A holistic and adaptive approach, integrating both local and global aspects, has proven to be key to successful HR management. These findings are expected to provide insights for HR practitioners in designing relevant policies to achieve the organization's long-term objectives. This research also contributes to the development of HR management theory by emphasizing the importance of synergy between technology, policies, and cultural management in addressing global challenges.